Quand l’usage fait patrimoine. Vers une patrimonialisation des usages et des paysages culturels ? - Stéphanie De Carrara; Yves-François Le Lay (Développement Durable et Territoires)
Intersection between law and practice, local usages influence not only every person’s cognitive knowledge but also their environmental actions. Thus they contribute to form and maintain cultural landscapes, which are the product of the intimate relationship linking the societies to their environment. By leaning on a corpus of 129 local usages books published during the 19th and 20th centuries and especially on the example of the Dombes, this paper tries to show how they are subjected to a multiplicity of processes that make them a heritage. Local usages patrimonialize knowledge and savoir-faire that favour the maintenance of the species, the landscapes and the identities. In this way and although they stay at the lowest rank of the French legal sources hierarchy, they guarantee the sustainability of socio-environmental elements which patrimonial value may be high, such as the fishponds of the Dombes region.